Fibromyalgia: do I tackle you with pharmacological treatments? - Serge Perrot (PAIN Reports)
Abstract. Pharmacological approaches are frequently proposed in fibromyalgia, based on different rationale. Some treatments are proposed to alleviate symptoms, mainly pain, fatigue, and sleep disorder. Other treatments are proposed according to pathophysiological mechanisms, especially central sensitization and abnormal pain modulation. Globally, pharmacological approaches are weakly effective but market authorization differs between Europe and United States. Food and Drug Administration–approved medications for fibromyalgia treatment include serotonin and noradrenaline reuptake inhibitors, such as duloxetine, and pregabalin (an anticonvulsant), which target neurotransmitter modulation and central sensitization. Effect of analgesics, especially tramadol, on pain is weak, mainly on short term. Low-dose naltrexone and ketamine are gaining attention due their action on neuroinflammation and depression modulation, but treatment protocols have not been validated. Moreover, some treatments should be avoided due to the high risk of abuse and severe side effects, especially opioids, steroids, and hormonal replacement.